Abandono familiar y sus repercusiones depresivas en residente adulto mayor - López Parrales, Génesis Nicole (2019)
The following work includes what is a psychological case study focused on the elderly, this was carried out in the gerontological center of good living in Quevedo. Where he was treated with the adult Juan (fictitious name) of 75 years of age, where he proceeded to work with him, through various psychological techniques to discover in which situation the subject was maintained, a diagnosis that in the process of this work is described. Therapies with a cognitive behavioral approach were carried out, that is, what daily activities were applied to be able to strengthen the adult's skills, likewise, mastery and pleasure techniques were developed, the Geronto gymnastics that was used to strengthen the patient's mobility and participation with others. All these written situations will be what will be discovered in the course of the case study and it will be known that what the problem really is, how it goes unnoticed and what its serious consequences are